KALININGRAD SPECIAL ECONOMIC ZONE: RESULTS AND PERFORMANCE Pavel P Bogdanenko - Pavel P. Bogdanenko (Модернизация, инновация, развитие)
The subject of the article is Russian special economic zones.InstituteofSpecial EconomicZones in theRussian Federationis known since the late 80-es of the last century. In some regions, in order to attract additional investments the first SEZ were created. And, as a result, despite a series of setbacks in some parts of the country, it has been shown that special economic zones can be an effective tool for economic development. An example of one of the most successful zones is theKaliningradspecial economic zone, established in 1991. The role of its residents in gross regional product per twenty-four years has become quite significant. The purpose of this work is to show the results of operations of Kaliningrad SEZ and its value among other Russian SEZs.The methodological base of the research is comparative analysis, cause-effect relationships, as well as historical method. The current results of its operations, as well as the structure of investment by industry are presented in this article. In addition, the author analyzes specialization and the results of development of zones that are under the control of the state-owned JSC “SEZ”. Despite the declared in 2008 by the government priority of high-tech and innovative industries, mainly industrial production zones have been developed in our country, but not technical innovation ones. Thereby touristic recreation and port zones are still deprived of sufficient investor attention. Among industrial production special economic zones, in terms of development, we can highlight zones in theLipetskregion (SEZ “Lipetsk”) and theRepublicofTatarstan(SEZ “Alabuga”). The main indicators of these industrial production zones are compared with those of the SEZ in theKaliningradregion. And as shown by this analysis, the Kaliningrad SEZ is the most developed SEZ, and is the “locomotive” of all Russian special economic zones: all its indicators exceed the values in two other analyzed areas, and the majority – more than their total value.